2011
DOI: 10.3233/jad-2011-110005
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibitors Improve Both Memory and Complex Learning in Aged Beagle Dogs

Abstract: Similar to patients with Alzheimer’s disease (AD), dogs exhibit age-dependent cognitive decline, amyloid-β (Aβ) pathology, and evidence of cholinergic hypofunction. The present study sought to further investigate the role of cholinergic hypofunction in the canine model by examining the effect of the cholinesterase inhibitors phenserine and donepezil on performance of two tasks, a delayed non-matching-to-position task (DNMP) designed to assess working memory, and an oddity discrimination learning task designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…The cloning, sequencing and expression of APP isoforms and the enzymes related to their processing also parallel the findings in human brain [100]. The dogs also show cholinergic hypofunction similar to that seen in human AD brain, suggesting that this model could be used for therapeutic screening as well as understanding the links between cholinergic functioning, Aβ pathology, and cognitive decline [101]. …”
Section: The Canine Model For the Study And Treatment Of Oxidativementioning
confidence: 87%
“…The cloning, sequencing and expression of APP isoforms and the enzymes related to their processing also parallel the findings in human brain [100]. The dogs also show cholinergic hypofunction similar to that seen in human AD brain, suggesting that this model could be used for therapeutic screening as well as understanding the links between cholinergic functioning, Aβ pathology, and cognitive decline [101]. …”
Section: The Canine Model For the Study And Treatment Of Oxidativementioning
confidence: 87%
“…The higher anticholinesterase activity of xanthohumol in comparison to isoxanthohumol was probably due to the differences in the structures of the two prenylated chalcones (lack of the central heterocyclic ring in xanthohumol). Very efficient inhibitors, such as donepezil or phenserine [Araujo et al, 2011], contain a short aliphatic fragment between the phenol rings. The increased bending of the molecule could positively influence the anticholinesterase activity of such compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work with these drugs has suggested possible dosage ranges for behavioral experiments [8,9,10,11,12], but the optimal dosage range for each drug is still unknown. Indeed, several previous studies with nonselective cholinergic drugs have observed a limited range of beneficial efficacy for improving memory, a range that varies across individuals, or a strong link between performance during control conditions and the degree of cognitive benefit from cholinergic enhancement [13,14,15,16]. Accordingly, identifying M 1 - or M 4 -selective drugs that improve memory performance in a general experimental population will likely depend on the use of different doses and taking subject differences in baseline memory performance into account.…”
Section: Introductionmentioning
confidence: 99%